2017
DOI: 10.2196/jmir.8033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Screen-to-Screen Versus Face-to-Face Consultation on Doctor-Patient Communication: An Experimental Study with Simulated Patients

Abstract: BackgroundDespite the emergence of Web-based patient-provider contact, it is still unclear how the quality of Web-based doctor-patient interactions differs from face-to-face interactions.ObjectiveThis study aimed to examine (1) the impact of a consultation medium on doctors’ and patients’ communicative behavior in terms of information exchange, interpersonal relationship building, and shared decision making and (2) the mediating role of doctors’ and patients’ communicative behavior on satisfaction with both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 69 publications
2
64
0
3
Order By: Relevance
“…Many mHealth apps offer platforms for telemedicine to facilitate doctorpatient communication, which is cost-effective and timely [37]. A study explored doctor-patient communication through screen-to-screen versus face-to-face consultations showed no significantly different results regarding the quality of doctor-patient communication [38]. However, using mHealth apps without human interactions cannot replace seeing a GP.…”
Section: Discussionmentioning
confidence: 99%
“…Many mHealth apps offer platforms for telemedicine to facilitate doctorpatient communication, which is cost-effective and timely [37]. A study explored doctor-patient communication through screen-to-screen versus face-to-face consultations showed no significantly different results regarding the quality of doctor-patient communication [38]. However, using mHealth apps without human interactions cannot replace seeing a GP.…”
Section: Discussionmentioning
confidence: 99%
“…A survey among urologists in the United States found that 28% used social media for professional purposes [18]. Social media allows physicians to interact with their patients, regardless of geography or time [19]. Social media also give patients a more active role in disease management [20].…”
Section: Discussionmentioning
confidence: 99%
“…This will place female patients in a position that they are not able to state all their problems and can ultimately lead to failure of high-quality treatment. Moreover, another study found that patients had a better experience with a female doctor than a male doctor when it involved shared decision-making (Tates et al 2017). In other words, female doctors created a more comfortable environment for patients than male doctors to open up and make health decisions cooperatively.…”
Section: Interruption and Doctor-patient Interactionmentioning
confidence: 99%